USP15 promotes the apoptosis of degenerative nucleus pulposus cells by suppressing the PI3K/AKT signalling pathway - Yu, Bin (J Cell Mol Med, 2020)
OBJECTIVES: Degenerative disc disease is characterized by an enhanced breakdown of its existing nucleus pulposus (NP) matrix due to the dysregulation of matrix enzymes and factors. Ubiquitin‐specific protease 15 (USP15) is reported to be abnormal in certain human diseases. However, its role in NP degeneration remains unclear. Therefore, we aimed to explore the function of USP15 in degenerative NP cell specimens. METHODS: We induced gene silencing and overexpression of USP15 in degenerative NP cells using RNA interference (RNAi) and a lentiviral vector, respectively. qRT‐PCR and Western blotting were used to determine gene and protein expression levels. Cell apoptosis was analysed via flow cytometry. Protein interaction was examined by performing a co‐immunoprecipitation assay. Furthermore, the PI3K inhibitor LY294002 and agonist IGF‐1 were used to investigate the link between USP15 and AKT in NP degeneration. RESULTS: We found that USP15 was up‐regulated in degenerative NP cells and that its overexpression accelerated the process of apoptosis. Moreover, USP15 expression levels negatively correlated with AKT phosphorylation in degenerative NP cells. Furthermore, targeting and silencing USP15 with miR‐338‐3p and studying its interaction with FK506‐binding protein 5 (FKBP5) revealed enhancement of FKBP5 ubiquitination, indicating that USP15 is a component of the FKBP5/AKT signalling pathway in degenerative NP cells. CONCLUSIONS: Our results show that USP15 exacerbates NP degradation by deubiquitinating and stabilizing FKBP5. This in turn results in the suppression of AKT phosphorylation in degenerative NP cells. Therefore, our study provides insights into the understanding of USP15 function as a potential molecule in the network of NP degeneration.